2010
DOI: 10.3141/2144-03
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Modal Variability in Effects of Gasoline Prices on U.S. Transit Ridership

Abstract: Previous research has shown a relationship between gasoline price and public transportation use. Although the magnitude, direction, and volatility of this relationship vary by mode, location, and system size, there can be no doubt that recent fuel price growth and fluctuation have affected most U.S. transit systems. The research presented here explores the relationship between transit ridership and fuel price, among other operational and external factors. This investigation found that after seasonal effects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…16 Haire and Machemehl studied five major U.S. cities; Atlanta, Dallas, Los Angeles, San Francisco and Washington, D.C. and found that as fuel prices increase by 1%, transit demand on average increases 0.24%. 17 This represented a larger increase than other studies have found and is likely related to the higher service levels in these cities.…”
Section: Elasticity Of Transit Demand With Respect To Gas Pricesmentioning
confidence: 59%
See 1 more Smart Citation
“…16 Haire and Machemehl studied five major U.S. cities; Atlanta, Dallas, Los Angeles, San Francisco and Washington, D.C. and found that as fuel prices increase by 1%, transit demand on average increases 0.24%. 17 This represented a larger increase than other studies have found and is likely related to the higher service levels in these cities.…”
Section: Elasticity Of Transit Demand With Respect To Gas Pricesmentioning
confidence: 59%
“…45 Haire and Machemehl that the found effect of gas prices on bus ridership varies regionally and as gas prices increase in the north central and Midwest U.S., ridership there falls. 46 The lack of regional consistency in the research suggests geographic considerations in the gas price and transit demand relationship are either not relevant or well understood.…”
Section: Transit Service Geography and Urban Environmentmentioning
confidence: 96%
“…Several studies have been developed to determine the success factors that contribute to increasing increase in transit ridership. For example, Haire and Machemehl (2010) has pointed out the impacts of fuel prices on ridership. The introduction of new technology such as autonomous driving technology will play an essential role in increasing ridership for public transport system without decreasing the fare revenue.…”
Section: Ridershipmentioning
confidence: 99%